A Ricoeur-Inspired Approach to Interpret Participant Observations and Interviews - Simonÿ, Charlotte (Glob Qual Nurs Res, 2018)
In-depth knowledge of what it means to patients to receive health care services is crucial to the development of adequate protocols for nursing. Qualitative research allows us to gain important insight into what is experienced by and meaningful to patients. The French philosopher Paul Ricoeur’s thoughts have inspired qualitative researchers to conduct various forms of analysis and interpretation that increase our knowledge of ways of being-in-the-world. This article describes and discusses how a specific approach to derive in-depth knowledge of patients’ lived experiences can be taken. A combination of participant observations and interviews was used to generate data. Field notes and transcribed interviews were gathered as one collective text and analyzed and interpreted with inspiration from Ricoeur’s thoughts on narratives and interpretation. This approach is argued to be a significant way of developing in-depth knowledge of patients’ lived experiences. Such knowledge is important within nursing science.